Innovation in sweet rice wine with high antioxidant activity: Eucommia ulmoides leaf sweet rice wine - Ren, Na; Gong, Weiwei; Zhao, Yichen; Zhao, De-gang; Xu, Yiwen (Frontiers in Nutrition, 2023)
The dried leaves of Eucommia ulmoides Oliv., which have a high nutritional value, are mainly used in both medicine and food. In this study, we used Eucommia ulmoides leaf superfine powder as an additive in the fermentation of glutinous rice (Semen Oryzae Glutinosae) to develop a new healthcare product, Eucommia leaf sweet rice wine. The fermentation conditions were optimized, and the nutrient value was evaluated through analyses of metabolites, functional compositions, antioxidant capacity, and antihyperglycemic, antihyperlipidemic, and antihypertensive abilities. The metabolic analysis demonstrated that Eucommia leaf sweet rice wine contained a large number of flavonoids and other metabolites. Eucommia leaf sweet rice wine had higher contents of flavonoid (729.0 ± 0.11 μg/g), free amino acids (55.0 ± 0.37 μg/g), polyphenol (150.0 ± 0.43 μg/g), and polysaccharide (0.25 ± 0.03 μg/g) than traditional sweet rice wine, with increases of 14.7, 2.6, 6.8, and 6.3 times, respectively. In addition, an analysis of antioxidant capacity in vitro revealed that Eucommia leaf sweet rice wine had a high level of activity in scavenging 2, 2-diphenyl-1-picrylhydrazyl (DPPH), superoxide anion, and hydroxyl radicals, as well as in reducing iron, indicating that it was a strong antioxidant. Furthermore, Eucommia leaf sweet rice wine had a high cholate binding capacity and could significantly inhibit α-amylase, α-glucosidase, and angiotensin-converting enzyme (ACE) activity. In conclusion, this study developed a new application of Eucommia leaf in sweet rice wine fermentation and brewed Eucommia leaf sweet rice wine with strong antioxidant activity and positive antihypertensive, antihyperglycemic, and antihyperlipidemic effects in vitro. This study suggests new opportunities for the wider use of Eucommia ulmoides leaves and adds variety to sweet rice wine.